Cause analysis and countermeasure of blockage in urea pyrolysis denitration system of coal-fired power plant. Issue 2 (February 2021) - Yao, Yongqi; Gui, Sha; Yang, Jiaxian; Wei, Jianbo; Zhang, Wen; Li, Peipei; Xue, Fangming; Su, Jingcheng; Liu, Xiuru
Abstract: Due to the safety and convenience storage of raw materials and the maturing technology, the method of urea pyrolysis for ammonia has been widely used in the selective catalytic reduction (SCR) denitration technology of thermal power plants. However, crystallization and blockage phenomennons occured frequently, seriously disrupting the normal operation of SCR denitrification systems. In order to analysis the reasons of crystallization plugging in urea pyrolysis process, This paper collects and analyzes the scaling samples from pyrolysis furnace and spraying ammonia pipe to identify scaling substances, analyzes the reasons of urea crystallization, puts forward the improvement measures so as to guarantee the safety and steady operation of SCR-DeNOx system.